2022
DOI: 10.1097/inf.0000000000003525
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Bacterial Colonization and Mucosal Responses Between High and Low SES Children in Indonesia

Abstract: Background: Increased nasopharyngeal carriage of pathogenic bacteria is found in low socioeconomic status (SES) settings. How SES affects local immune responses, important for controlling colonization, is currently unknown. Objective: Examining bacterial colonization and cytokine response in the nasal mucosa of children from high and low SES. Methods: Nasosorption samples were collected in October 2019 from 48 high SES and 50 low SES schoolchildren, in a cross-sectional study in Makassar, Indonesia. Twenty-fiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
(53 reference statements)
1
0
1
Order By: Relevance
“…In the school serving the low SES areas, more children were infected with intestinal helminths. However, the prevalence of helminths found in the current study is lower than what has been reported before in the same school(Amaruddin et al, 2022; Hamid et al, 2015), which can be accounted for by the recent regular de worming programs at schools. It is possible that light infections were still present but could not be detected due to the limited sensitivity of the Kato Katz method used (Tarafder et al 2010).…”
contrasting
confidence: 82%
See 1 more Smart Citation
“…In the school serving the low SES areas, more children were infected with intestinal helminths. However, the prevalence of helminths found in the current study is lower than what has been reported before in the same school(Amaruddin et al, 2022; Hamid et al, 2015), which can be accounted for by the recent regular de worming programs at schools. It is possible that light infections were still present but could not be detected due to the limited sensitivity of the Kato Katz method used (Tarafder et al 2010).…”
contrasting
confidence: 82%
“…Moreover, in Indonesian schoolchildren SES was identi ed as the main driver for differences in microbiota composition (Amaruddin et al, 2020), which is an important determinant for immune responses to vaccination (Lynn et al, 2022). Previously, in children from the same cohort as the current study, we showed that SES also affects the mucosal immunity, as increased nasal colonization with potentially pathogenic bacteria and altered nasal cytokine responses were seen in low versus high SES children from Makassar (Van Dorst et al, 2022). Understanding the differences in the peripheral immune pro les of populations living in high or low socioeconomic segment of society within one city can be important in explaining discrepancies in health outcomes and in vaccine responsiveness.…”
Section: Introductionsupporting
confidence: 55%